Snake venom toxins: toxicity and medicinal applications - Chan, Yau Sang; Cheung, Randy Chi Fai; Xia, Lixin; Wong, Jack Ho; Ng, Tzi Bun; Chan, Wai Yee (Applied microbiology and biotechnology, 2016)
Snake venoms are complex mixtures of small molecules and peptides/proteins, and most of them display certain kinds of bioactivities. They include neurotoxic, cytotoxic, cardiotoxic, myotoxic, and many different enzymatic activities. Snake envenomation is a significant health issue as millions of snakebites are reported annually. A large number of people are injured and die due to snake venom poisoning. However, several fatal snake venom toxins have found potential uses as diagnostic tools, therapeutic agent, or drug leads. In this review, different non-enzymatically active snake venom toxins which have potential therapeutic properties such as antitumor, antimicrobial, anticoagulating, and analgesic activities will be discussed.